A1.5 Rheumatoid arthritis alters the preservative role of IL-15 on bone-marrow-resident TREG cells towards a pro-inflammatory phenotype. (13th February 2015) - Massalska, M; Kuca-Warnawin, E; Radzikowska, A; Musialowicz, U; Skalska, U; Plebanczyk, M; Burakowski, T; Maldyk, P; Kontny, E; Maslinski, W
Abstract : Background and objectives: Inflammatory process observed in bone-marrow (BM) of RA patients (called bone marrow oedema) together with autoantibodies production was shown to precede joint destruction in RA. Natural producers of IL-15 in bone marrow are mesenchymal stromal cells and locally overproduced IL-15 was proved to elevate recently activated T cells number. In the present work we show increased production of main pro-inflammatory cytokine TNF by otherwise suppressive Treg cells (Tregs) isolated from bone marrow of RA patients. Materials and methods: Bone marrow samples were obtained from RA and OA patients as a standard procedure during hip bone replacement surgery. Isolated bone marrow mononuclear cells (BMMC) were stimulated by IL-15 in 72 h in vitro culture before isolation of CD4 + CD25 + ++ Tregs and CD4 + CD25 - responder T cells (Tresp) by cells sorter for functional activity measurement. TNF and IFN-gamma were estimated by specific ELISA in the supernatants removed before addition of [ 3 H] thymidine in proliferation assays. Data are shown as mean ± SEM. Results: Concentration of TNF produced by Tregs isolated from RA BM was comparable with TNF produced by responder T cells (14.2 ± 2.7 pg/ml in Tregs vs. 12.7 ± 1.8 pg/ml in Tresp) and higher then TNF produced by Tregs isolated from OA BM (8.5 ± 3.1 pg/ml) or healthy volunteers blood (7.7 ± 1.9 pg/ml). However, despite high TNF production, Tregs from RA BM remain functionally active and suppress proliferation, TNF and IFN-gamma production in coculture with Tresp. In RA number of Tregs as well as Foxp3 MFI was increased by IL-15 stimulation but TNF production stayed at the same level (11.6 ± 4.7 after IL-15 treatment vs. 14.2 ± 2.7 without IL-15 treatment). However, when the cells were additionally stimulated by anti-CD3/CD28, TNF production by Tregs significantly increased (42.6 ± 7.4 vs. 15.2 ± 4.8; p = 0.043) after IL-15 stimulation. Conclusions: IL-15 overproduced in bone marrow of RA patients may exert opposite effects on Tregs – increase number and Foxp3 expression from one side and increase TNF production from the other. Thus Treg present in RA BM share suppressive capacities with pro-inflammatory feature, that may contribute to RA pathogenesis.